IDENTIFIKASI PROBLEMATIKA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Rainatul Agustina, Nadya; Qudni, Darul; Salamah, Hj. Salamah (CV. Lafadz Jaya, 2024)
Like education in general,Islamic Religious Education which is part of a whole education in the sphere of school also experiences similar problems. Responding to the emergence of problems in the learning process of Islamic Religious Education (PAI), many theoretical theoretical studies on learning problems have been put forward by researchers. Mentioned problems/problematics in Islamic Learning are: Problems in learners that often arise are the lack of ability to ability to read Arabic writing, problems of difficulty in memorising material, lack of enthusiasm/motivation to learn and problems in understanding the material presented. enthusiasm/motivation to learn and problems in understanding the material presented. This research uses the library research method, the data collection technique used in this research is literature data collection, namely by collecting data. The data collection technique used in this research is the collection of literature data, namely by collecting materials that are continuous with the object of discussion under study. researched. This method is intended to analyse the entire discussion of the problematic learning of Islamic Religious Education (PAI). As a process, learning is faced with a variety of problems, problematics. Learning problems are various problems that interfere, hinder, complicate, or even cause failure in achieving learning goals. result in failure in achieving learning objectives. Problematics learning can be traced from the course of the basic learning process. In general, the learning process can be traced from the factors that influence the learning process. The success of learning is determined by 3 main factors, namely materials (raw input), instruments and environment. The results of this study, It can be concluded that seen from several aspects, namely students, educators, infrastructure and environment. As well as the solution to the problem with the solution which will be able to overcome the problems that occur, just the willingness of the heart to overcome the problems that occur. problems that occur, just the willingness of the heart to change and overcome the problems that occur in the scope of education in schools. problems that occur within the scope of education in schools.